Impactos e impressões da qualidade vocal do professor no contexto da sala de aula - Ana Luiza Vilar Rodrigues (2016)
Purposes: identify the impacts of teachers voice in classroom and analyze and compare the perception of students, teachers and lay people regarding the preferred and non-preferred voices for an elementary school teacher. Methods: two kinds of investigation were performed a literature review and an observational cross- sectional study. The literature review was guided by the following question What is the impact of dysphonic voice in the classroom? and was performed using the databases MEDLINE via PubMed, Lilacs and IBECS via VHL Research Portal, Web of Science and references described inthe selected studies. The follow terms were used: voice disorders, dysphonia, dysphonic voice, voice quality, joined by the Boolean operator AND to language tests, comprehension, speech perception and cognition. The cross-sectional study analyzed and compared the judgment of a preferred voice for an elementary school teacher, by 104 students and 40 teachers of a public school of Belo Horizonte and 40 lay people from the same city. It was created, as a tool research, a voice bank consisting of 14 types of voice and a questionnair for making vocal preference and voices psychodynamics. Results: The articlesfound in the literature review showed negative impact of teachers dysphonic voice in the classroom, especially in noisy environments and the importance of slow speech rate for better understanding of the message in classroom. The results of the cross-sectional study showed that students, teachers and lay people prefer for an elementary school teacher neutral quality voices (95.1%), bass pitch (75%) and low speed rate (67.9%) and those voices presented positive vocal psychodynamic, regarding pleasantness, motivation and ability to attract attention. The least favorite voices for this population were the voices of moderate breathy (98.4%), intense breathy (97.3%), slight roughness (94.6%),intense roughness (94.6%), moderate roughness (94.0%) and imprecisearticulation (94.0%) and those voices were negatively availed in relation to vocal psychodynamic regarding pleasantness, motivation and ability to attract attention. Conclusion: The teacher dysphonia difficults the understanding the message by the students and is valued by them negatively. The slow speech rate of teaching enhances the communication in the classroom. The preferred voices for a teacher of elementary school by students, teachers and lay people are the voices of neutral quality, slow speed rate and bass pitch that associatedpositively with a vocal psychodynamic of pleasantness, motivation and ability to attract attention. The voices of rough and breathy vocal quality or that have an inaccurate articulation are perceived negatively and do not arouse attention, motivate or are nice